(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
For at least three decades now, some Kenyan linguists have been advocating the teaching of a local, Kenyan accent of English, instead of the British English accent commonly known as Received Pronunciation, RP. Their key argument is that RP as a model cannot simply be achieved as an educational goal in Kenya because a local, widespread, and stable pronunciation has developed in Kenya. The present paper joins the fray of this argument by justifying it in greater detail and basing it on updated information on the status of RP. At the core of this expanded justification are two main observations: firstly, the traditional inventory of RP sounds that has long been taught in Kenya is now a confusing list across British English dictionaries and linguists’ publications, as a result of the changes it has undergone in Britain: in some cases “new” vowel phonemes have been added by some, while in others one or two phonemes have been “replaced” with others. Secondly, and more importantly, Kenyan English usage has significantly simplified the various segmental and suprasegmental aspects of British RP, so much so that it does not make much sense to continue using it as the reference for teaching and examination. Nonetheless, the paper also stresses the fact that despite all this, British RP still enjoys a mythical status among many Kenyan linguists, teachers of English, and decision-makers, and, hence, cannot simply be wished away. That is why the paper proposes that what should be taken as the reference in Kenyan schools, for being a good reflection of mainstream Kenyan English pronunciation, should be labelled “Kenyan-indigenised RP”, given the extent of its simplification.